Development and Validation of an LC-MS/MS Method for the Determination of Plasma and Red Blood Cell Omega Fatty Acids: A Useful Diagnostic Tool - Lénárd Farczádi; Minodora Dobreanu; Adina Huțanu; Silvia Imre (Separations, 2024)
Background: LC-MS is an ever-increasingly used methodology for clinical applications. Due to the superior selectivity and sensitivity, in certain situations, it can offer an advantage or be the only option for diagnostics and biomonitoring applications. Methods: A high selectivity sensitive LC-MS/MS method was developed for direct quantification of free plasma polyunsaturated fatty acids as well as conjugated membrane polyunsaturated fatty acids, using isocratic reverse phase elution. A quick and simple sample purification method was used in order to ensure high-throughput analysis of biological samples. The method was validated with regard to selectivity, sensitivity, linearity, accuracy, precision, carryover, and recovery, as well as other relevant parameters. Results and Conclusions: The method was developed and validated with respect to all relevant parameters and was successfully used in a number of clinical diagnostics and biomonitoring applications. The simple sample purification process allowed for an easy learning curve for analysts and other users, while ensuring a low chance of systematic or random errors and thus reliable results usable in a clinical setting.